Keanekaragaman dan Peran Fungsional Jamur Rhizosfer Tanaman Lada (Piper nigrum L.) Berdasarkan Pendekatan Metagenomik di Banjarnegara, Jawa Tengah - Wicaksono, Danar; Poerwanto, Mofit Eko; Ulilalbab, Azizah Ridha; Ajri, Miftahul; Kawuryan, Siwi Hardiastuti Endang (Universitas Wiralodra, 2025)
Black pepper (Piper nigrum L.) is a high-value spice crop whose productivity is strongly influenced by plant health and the microbial conditions in the rhizosphere. This study aimed to characterize the fungal communities in the rhizosphere of healthy black pepper plants grown in fields with a history of pest and disease outbreaks, using a metagenomic approach based on ITS1 sequencing via the Illumina platform. Rhizosphere soil samples were collected from healthy black pepper plants in a plantation located in Tribuana Village, Banjarnegara, Central Java, which had experienced pest and disease incidences in the previous growing season. Taxonomic composition, relative abundance, and diversity indices (Shannon, Simpson, and Richness) were analyzed. The results revealed that the fungal community was dominated by organic matter- decomposing fungi (57.29%), followed by plant growth- promoting fungi (PGPF) at 19.82%. These two groups not only exhibited quantitative dominance but also showed high diversity and evenness values, indicating ecological stability within the root system of healthy pepper plants. These findings highlight the importance of cultivation practices that support the persistence of functional microbial communities, such as organic matter amendments and the application of biofertilizers. In conclusion, the high dominance and diversity of decomposer fungi and PGPF in the rhizosphere of healthy black pepper plants underscore their critical role in maintaining plant health and provide a scientific basis for sustainable soil management strategies. Pathogenic fungal communities accounted for 12.76% of the total abundance, exhibiting moderate diversity and relatively high evenness.